2016
DOI: 10.4235/agmr.2016.20.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Performance for Bystanders’ Cardiopulmonary Resuscitation in Geriatric and Out-of-Hospital Cardiac Arrested Patients

Abstract: Background: The purpose of this study was to determine if there were changes in bystanders' chest compression performance and activation of emergency medical services in geriatric and out-of-hospital cardiac patients following the institution of the 2010 International Resuscitation Guidelines and 2008 Good Samaritan Law in South Korea. Methods: This is a retrospective observational study using medical records, and including patient charts and an Utstein Style database in a tertiary hospital. We analyzed the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…During this time period, in addition to the current BLS provider courses, we would also like to conduct BLS instructor courses, ACLS courses, and PALS courses. Similar to the experience of Korea in increasing the in-hospital survival rate from 17.2% in 2005 to 28.5% in 2009 (25), increasing the rate of bystander chest compression from 7.78% to 20.13% between 2005 and 2009 to 2010 and 2014 (26), and the addition of qualified heart savers by paramedics and analysis of resuscitation training effects (27, 28), Vietnam’s indicators on this issue will also likely change in the future.…”
Section: Resultssupporting
confidence: 59%
“…During this time period, in addition to the current BLS provider courses, we would also like to conduct BLS instructor courses, ACLS courses, and PALS courses. Similar to the experience of Korea in increasing the in-hospital survival rate from 17.2% in 2005 to 28.5% in 2009 (25), increasing the rate of bystander chest compression from 7.78% to 20.13% between 2005 and 2009 to 2010 and 2014 (26), and the addition of qualified heart savers by paramedics and analysis of resuscitation training effects (27, 28), Vietnam’s indicators on this issue will also likely change in the future.…”
Section: Resultssupporting
confidence: 59%
“…However, various studies on the survival rate of patients who experience cardiac arrest have demonstrated that as the age of a patient who experiences cardiac arrest increases, the likelihood that he or she will survive after cardiopulmonary resuscitation (CPR) decreases. [3][4][5][6] The "Chain of Survival" as an essential component of a series of actions designed to reduce mortality associated with cardiac arrest and includes early arrest recognition and emergency activation, early CPR, early defibrillation, expert advanced life support, and integrated postresuscitation care. 7,8) Survival rates and favorable neurologic outcomes of patients who experience cardiac arrest are closely related to the quality of chest compressions during CPR.…”
Section: Introductionmentioning
confidence: 99%
“…However, various studies on the survival rate of patients who experience cardiac arrest have demonstrated that as the age of a patient who experiences cardiac arrest increases, the likelihood that he or she will survive after cardiopulmonary resuscitation (CPR) decreases. 3 6) …”
Section: Introductionmentioning
confidence: 99%
“…When emergency situations occur that induce stopping of the heart (e.g., drowning or cardiac arrest), it is important to perform the correct cardiopulmonary resuscitation (CPR) process as soon as possible to recover the autonomic beating of the native heart and prevent serious brain damage [ 1 ]. When such an emergency situation occurs in locations outside of a hospital due to accidents or disease, emergency services should be immediately contacted and manual CPR process needs to be performed repetitively until the arrival of the trained paramedics.…”
Section: Introductionmentioning
confidence: 99%